Factors Influencing The Implementation Of Clean And Healthy Living Behavior Of Families In The Hamlet Of Kampung Baru Of Sumber Agung Village In The Sub-District Of Kalaena Of The East Luwu Regency In 2020 - Risal, Muhammad; Rauhun, Siti; Sali, Adrian; Murtiningsih, Murtiningsih (Jurnal Ilmu Kesehatan, 2022)
Abstract Clean and Healthy Living Behavior (CHLB) is all health behavior that is carried out with awareness so that family or family members can help themselves in the health sector and play a pivotal role in health activities in the community. The CHLB aims to increase the ability of families to carry out the CHLB and participate actively in the health movement of the community. The purpose of the study is to investigate the influence of knowledge and education towards the implementation of the CHLB of family in the hamlet of Kampung Baru of Sumber Agung village, in the sub-district of Kalanea, East Luwu Regency in 2020. This study is a descriptive-analytic study with a cross-sectional approach to determine the relationship between the independent and dependent variables. This research was conducted from July to August 2020 with a total population of 171 respondents and a sample of 63 respondents. The results of the study using the chi-square test obtained the score of knowledge pv = 0.000 (pv < 0.005), meaning that there was a relationship between knowledge and Clean Living Behavior. Meanwhile, the score of education with the chi-square test was 0.003 (pv < 0.005), which means that there was a relationship between education and Clean and Healthy Living Behavior. Based on the results of this study, the family members are suggested to always conduct clean and healthy living behavior in order to maintain health in the family.